Gold(I)‐Catalyzed 6‐endo‐Dig Hydrative Cyclization of an Alkyne‐Tethered Ynamide: Access to 1, 6‐Dihydropyridin‐2(3H)ones. Issue 29 (20th June 2013) - Ghosh, Nayan; Nayak, Sanatan; Sahoo, Akhila K.
<x xml:space="preserve">Abstract</x> Hydrate your chemistry! Hydrative cyclization of 5‐yne‐ynamides in the presence of Echavarren's catalyst and p‐toluenesulphonic acid (PTSA)⋅H2O at room temperature affords an array of 1, 6‐dihydropyridin‐2(3H)one derivatives. Isomerization, epoxidation, and hydrogenation of the double bond and insertion of an extended π‐conjugate system into the pyridinone skeleton have been successfully accomplished (see scheme; Ts=tosyl).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>